Early Detection Level to Students Anxiety Using Fuzzy Sugeno Method - Nawindah Nawindah (FKOM UNIKU, 2025)
Anxiety disorders are generally common, especially in adolescents. In institutions that provide non-formal education such as Learning activity group or Sanggar Kegiatan Belajar (SKB), students often face complex problems ranging from family problems, problems in teaching and learning activities and problems at work. For this reason, further treatment is needed to overcome the problems faced. One of them is counseling activities, this activity is really needed to help students find the right solution. However, the teaching staff, both tutors and teachers who teach, do not yet have the basic knowledge to handle proper counseling. The importance of carrying out this research activity is that it can help students, teachers and leaders in overcoming student anxiety disorders which have an impact on teaching and learning activities. Tools are really needed to detect students who has mild, moderate or severe anxiety disorders and students who do not have anxiety. The aim of this research is to provide recommendations for students' anxiety levels using the DASS-21 tools. In this tool there are questions for anxiety that students must answer, consisting of 7 questions. The method used in this research is Fuzzy Sugeno. The contribution to this research recommends a model for early detection of student anxiety using Fuzzy Sugeno so as to eliminate ambiguity and uncertainty in the answers to existing questions. The implication of this research is that the Fuzzy Sugeno method is suitable for early detection of student anxiety with a high accuracy rate of 66.67% so that students can detect early the level of mental anxiety early. With the results of recommendations for anxiety levels, teachers can handle students and provide solutions to students easier and leaders can be a supporter in decision making